Retrieval of an Intracranially Migrated Dental Injection Needle Through the Foramen Ovale: 2-Dimensional Operative Video. Issue 2 (23rd October 2019) - Aoun, Salah G; El Ahmadieh, Tarek Y; Ban, Vin Shen; Patel, Vishal J; Vance, Awais; Patel, Ankur R; Tandon, Rahul; Zuniga, John R; Batjer, H Hunt; Barnett, Sam
Abstract: Dental injection needle migration is a rare complication of orthodontal procedures. When these needles fracture, they typically dislodge into the cervical space or the facial musculature. Migration into the cranial vault is difficult because of the obstacle created by the skull base. We report a rare case of intracranial migration of an anesthetic injection needle through the foramen ovale. A 59-yr-old man underwent the extraction of a right maxillary molar. The distal end of a 25-gauge injection needle broke into his pterygoid musculature, causing him pain while chewing. Vascular imaging obtained after a computed tomography scan of his face showed that the needle had migrated, potentially because of his efforts of mastication, and had traversed the foramen ovale into the middle cranial fossa. The patient started experiencing intermittent right facial numbness, likely due to compression or injury to the right trigeminal nerve. Our oral and maxillofacial colleagues did not believe that the needle could be retrieved from its facial end. The patient elected to undergo the recovery of the needle through a craniotomy given the fact that the object was contaminated and because he was becoming increasingly symptomatic. A right pterional craniotomy was planned. Extradural dissection was performed until the dura going into the foramen ovale was revealed. We could feel the metallic needle under the dural sheath of the trigeminal nerve. The dura was opened sharply directly over the needle. We then proceeded to mobilize the needle into the face, and then pulled it out completely through the craniotomy to avoid injury to the temporal lobe. The patient recovered well and was asymptomatic at the time of discharge. This case report was written in compliance with our institutional ethical review board. Institutional review board (IRB) approval and patient consent were waived in light of the retrospective and deidentified nature of the data presented in accordance with the University of Texas Southwestern (UTSW) IRB.